The Effect of Food Hardness on the Development of Dental Caries in Alloxan-Induced Diabetic Rats - Yutaka Nakahara; Tomoya Sano; Yasushi Kodama; Kiyokazu Ozaki; Tetsuro Matsuura (Journal of Diabetes Research)
We have previously shown that dental caries may be produced in diabetic rodent models fed with noncariogenic standard diets; however, many studies usually add large amounts of sugar to the diet to induce dental caries. Moreover, the physical properties of cariogenic diets have been reported as an important factor in the formation of caries. The aim of this study was to clarify the effect of the hardness of non-cariogenic diets on the development of dental caries in diabetic rodents. Seven-week-old female F344 rats were divided into 4 groups: intact rats fed with a standard pelletized or powdered diet and alloxan-induced diabetic rats fed with a standard pelletized or powdered diet. All of the rats were sacrificed at 52 weeks of age for morphological examinations on their dental tissue. Dental caries had developed and extended to all the molars in the diabetic rats that were fed with both the pelletized and powdered diets. Moreover, the lesion was significantly enhanced in the powdered diet group compared to that in the pelletized diet group. In conclusion, food hardness is an important factor influencing the development of dental caries in diabetic rats.